Penile Self-Amputation in a Patient with Schizophrenia, while on Clozapine Augmentation with Modafinil: A Case Report (Kerala Journal of Psychiatry, 2018)
Genital self mutilation is extremely rare and is seen in psychotic illnesses with associated risk factors like commanding hallucinations, religious delusions, past suicide attempts, depression, personality disorder, substance abuse or gender identity problems. We report a case of total penile self amputation in a 23 year old male without any of these risk factors. He was diagnosed with schizophrenia and was well maintained on clozapine 150 mg with with (an sos) prescription of modafinil 100mg in the morning. In human clinical trials, modafinil has no evidence for self mutilatory behaviour.
Keywords: Penile self amputation; self-mutilation in schizophrenia; modafinil